2019
DOI: 10.1126/sciadv.aav9879
|View full text |Cite
|
Sign up to set email alerts
|

Massive clonal expansion of medulloblastoma-specific T cells during adoptive cellular therapy

Abstract: Extensive clonal T cell expansion is associated with response to immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…It has been previously reported that spectratyping using fluorescence-activated cell sorting (FACS) analysis of TCR V may be used to track the reactivity of specific TCR V families towards target cells [43][44][45]. For validation of this method, we verified the reactivity of TCR V 5.1, 5.2 T-cells for OVA-expressing target cells [46] (Supp.…”
Section: Individual Tumor Escape Variants Are Immunologically Distincmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been previously reported that spectratyping using fluorescence-activated cell sorting (FACS) analysis of TCR V may be used to track the reactivity of specific TCR V families towards target cells [43][44][45]. For validation of this method, we verified the reactivity of TCR V 5.1, 5.2 T-cells for OVA-expressing target cells [46] (Supp.…”
Section: Individual Tumor Escape Variants Are Immunologically Distincmentioning
confidence: 95%
“…Tumor-reactive T-cells were generated as previously described [29][30][31]40]. For TOGA tumors were utilized identically to KR158B-luc tumors.…”
Section: Adoptive Cellular Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…We can also use DCs pulsed with a tumor RNA transcriptome to expand polyclonal tumor-reactive T cells during adoptive T cell therapies in medulloblastoma. 55 In general, DCs are the feasible option regarding the specific loading of treatment agents to achieve effective antitumor immunization, and further exploration of DCs in the immunotherapeutic treatment of medulloblastomas is warranted.…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…We can also use DCs pulsed with a tumor RNA transcriptome to expand polyclonal tumor‐reactive T cells during adoptive T cell therapies in medulloblastoma. 55 …”
Section: Immune Cell Landscape Of Medulloblastomamentioning
confidence: 99%